Performing at the interval: Perambulations of the maternal child in an Australian youth-based arts practice. Issue 2 (3rd July 2019) - Trezise, Bryoni
ABSTRACT: In this article I consider the performative moving sculpture titled 16 Girls (2015) produced by Australian-based organization St Martins Youth Art Center as a work that plays consciously and actively with the everyday social performativities of the girl-child-figure. It does so by using contemporary performance practices that engage techniques of Invisible Theatre to disrupt site-specific locations with augmented pedestrian choreographies. In this article, I suggest that the work forms choreographies that visually and physically punctuate relationships between urban environments and everyday social practices to invite new apprehensions of the "maternal child" – a figure who appears to own her own means of production and to thereby give birth to herself.